We Were in the Big One: Experiences of the World War II Generation - Parillo, Mark P. (Rowman & Littlefield Publishers, 2002)
World War II was truly the largest and greatest conflict in U.S. history. We Were in the Big One: Experiences of the World War II Generation is a collection of diary entries, letters, photographs, and other documents from that era. Carefully selected from the Eisenhower Library's World War II Participants Collection and other archives, this material-generated in response to the historical events themselves-reflects the mindset of the people who produced it. These documents shed light on one of the most important periods of American history. We Were in the Big One is one of the first books to make primary source material on this era widely available for use in the classroom. These contemporary documents reveal a great deal about the attitudes of the World War II generation toward matters such as gender, political beliefs, race, religion, social and cultural mores, and personal values. With a concise introduction and headnotes that introduce each document, Prof. Parillo provides an interpretive framework that puts the selections in context for students. Parillo shows how the war affected Americans across gender lines, across social and political spectrums, on the home front, and on the battlefield. This compelling text enables students to discover how the war truly influenced an entire generation of Americans. We Were in the Big One is an excellent resource for courses in American twentieth-century history, World War II, and U.S. social and cultural history.